The Impact of Risk and the Potential for Loss on Managers' Demand for Audit Quality* - Hurley, Patrick J.; Mayhew, Brian W.; Obermire, Kara M.; Tegeler, Amy C. (Contemporary Accounting Research, 2021)
ABSTRACT This study uses experimental economic markets to investigate the impact of risk and the potential for loss on managers' demand for audit quality. We posit that these two important contextual factors influence managers' audit quality preferences. We study these factors because they are ubiquitous to companies, and we focus on their influence on managers because managers continue to play a significant role in the auditor hiring process and we know relatively little about their auditor preferences. We predict that risk, the potential for loss, and their interaction will each decrease manager demand for high audit quality due to a desire to achieve greater reporting flexibility. Experimental results are consistent with our predictions; specifically, increased risk, the potential for loss, and to a lesser extent their interaction, significantly reduce managers' likelihood of hiring the best available auditor in the market. Path analysis indicates that this reduction in audit quality demand leads to increases in misreporting. Finally, we observe investors overpaying for assets to a greater extent when managers hire lower‐quality auditors. Our results show that the contextual factors of risk and the potential for loss, which are ubiquitous to companies, can reduce demand for audit quality, which can increase misreporting behavior and ultimately harm investors.